THE EFFECTS OF DIFFERENT EXERCISE-BASED INTERVENTIONS ON FUNCTIONAL FITNESS OF OLDER ADULTS - Paravlić, Armin; Marušič, Uroš; Gerževič, Mitja; Urzi, Felicita; Šimunič, Boštjan (Annales Kinesiologiae, 2017)
Ageing is a multifactorial process associated with several irreversible functional and cognitive alterations of human body and determined by genetic and environmental factors. We aimed to investigate the effects of three physical activity interventions of 40 independently living older adults before and after a 3-month training period. Thirty female (69.6 ± 5.3 years) and ten male (70.6 ± 5.4 years) participants were randomly assigned into a physical exercise group (PEG; N = 9), a concurrent physical and cognitive exercise group (PEG + COG; N = 10), a physical exercise with additional 10 g of BCAA daily supplementation group (PEG+BCAA; N = 11), and a control group (CG; N = 10). All three groups performed the same physical exercise program for 12 weeks, three days a week for 45 − 60 minutes per session. Pre- and post-measurements were performed using a standardized functional fitness assessment tool for older adults i.e. Senior Fitness Test battery, upgraded with the Four Square Step Test (FSST) and Grip Strength Test (GST). When intervention groups were pooled, we found moderate to low improvements in the Chair Stand Up, Timed Up and Go, FSST and Six-minute Walk Tests (all P < .001). However, those improvements were intervention-specific with highest improvements found in the PEG for the FSST (P = .004) and Six-minute Walk Test (P = .004); in the PEG + COG for the Timed Up and Go Test (P < .001); and in the PEG+BCAA for body mass (P = .012) and the Chair Stand Up Test (P < .001). Although the sample size was low, our study provides further evidence of different interventional exercise-based programs that can benefit the population of independently living older adults.